MUSEUM MANAGEMENT AND DIGITALISATION: A COMPARATIVE STUDY IN MUSEUMS OF MAKASSAR CITY - Sabila Kayla (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This study aims to analyze management and digitalization in two significant museums in Makassar City, namely Museum La Galigo and Museum Mandala, using a comparative study approach. Data at Museum La Galigo was collected through direct observation and recording of visitor activities to examine the implementation of digital technology in service processes and the delivery of information to visitors. Meanwhile, the focus at Museum Mandala was on analyzing the content and utilization of various digital media, including websites, social media, and videos as promotional and educational tools capable of reaching a wider audience. The results show that Museum La Galigo emphasizes internal digitalization, particularly for data archiving and visitor education efforts. However, several main challenges were identified, related to inadequate technological facilities and limited capacity of human resources proficient in digital technology. On the other hand, Museum Mandala is more active in utilizing external digital platforms to expand reach and enhance interaction with visitors and the general public. Overall, the digitalization implementation in both museums has a significant positive effect in improving visitor experience and supporting more effective cultural information management. Nonetheless, this study found an essential need for increasing human resource capacity and more comprehensive technology integration to ensure optimal and sustainable digitalization. The study recommends enhancing collaboration among relevant parties, developing technological infrastructure in museums, and providing technology-based management training to support more adaptive and modern museum management. It is expected that this study can serve as a valuable reference for digitalization development in other museums in Makassar City and beyond.